The difficulty in selecting patients for cytoreductive nephrectomy: An evaluation of previously described predictive models - Manley, Brandon J.; Tennenbaum, Daniel M.; Vertosick, Emily A.; Hsieh, James J.; Sjoberg, Daniel D.; Assel, Melissa; Benfante, Nicole E.; Strope, Seth A.; Kim, Eric; Casuscelli, Jozefina; Becerra, Maria F.; Coleman, Jonathan A.; et al. (Urologic oncology, 2017)
To externally evaluate a preoperative points system and a preoperative nomogram, both created to assess time to death after cytoreductive nephrectomy (CN). We identified 298 patients who underwent CN at our institution, a tertiary cancer center, between 1989 and 2015. To validate the points system, we compared reported overall survival (OS) for each criterion to observed OS in our cohort. To evaluate the nomogram, we prognosticated risk of death at 6 months after surgery for 280 patients with sufficient follow-up in our cohort and evaluated discrimination using area under the curve (AUC) and calibration. Decision curve analysis was performed to assess clinical utility of the nomogram. Significant differences in OS were observed between patients with and without 5 of 7 criteria on univariate analysis: low albumin (P<0.0001), high lactate dehydrogenase (P = 0.002), liver metastasis (P = 0.004), retroperitoneal lymphadenopathy (P = 0.002), and supradiaphragmatic lymphadenopathy (P = 0.019). Discrimination from the preoperative model, predicting death within 6 months of surgery was lower in our cohort (AUC = 0.65, 95% CI: 0.52–0.79) than the original publication (AUC = 0.76). Decision curve analysis demonstrated little benefit for applicability. Five previously defined risk factors are predictive of decreased OS after CN in our cohort. We found lower discrimination using the preoperative model and minimal clinical utility according to decision analysis in our study cohort. These findings suggest the need for improved models to aid patient stratification and consequent treatment choice. •A total of 5 of 7 preoperative risk factors were predictive of overall survival.•The complete model had an AUC of 0.65; 95% (CI: 0.52–0.79) in our cohort.•Decision curve analysis demonstrated little benefit for applicability.•Differences in patient selection and pathology may explain the differentiating factors.